Assessment of Peri-implant Bone Disorders Treatment by Bone Replacements: Histological and Immunhistochemical Analysis in the Rabbit Tibia - Asmaa Ali (Journal of Global Pharma Technology, 2018)
Aims: to assess the efficiency of bone replacements in peri-implant disorders formed in the rabbit tibia. Methods: Twenty-four rabbits used to receive 36 screws of implant in their tibia. A circular bone defect 6.1 mm in diameter/4 millimeter depth made in the rabbit tibia. Dental implant sgrew